Analisis Yuridis Tentang Tindak Pidana Kelalaian yang Mengakibatkan Hilangnya Nyawa Orang Lain - Fitri Ida Laela; La Ode Risman (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
So the problem is whether the judge's consideration is based on the elements of a criminal act. carried out continuously in the decision is correct and appropriate and whether the conviction given by the judge in the decision is correct. The data was processed qualitatively, while the conclusion was drawn using deduction logic. Based on the judge's consideration that the testimony of the witnesses' testimony of the defendant, documentary instructions and the existence of evidence and facts were revealed at the trial.